LHCb pentaquarks in constituent quark models - P.G. Ortega (Physics Letters B, 2017)
The recently discovered Pc(4380)+ and Pc(4450)+ states at LHCb have masses close to the D¯Σc⁎ and D¯⁎Σc thresholds, respectively, which suggest that they may have significant meson–baryon molecular components. We analyze these states in the framework of a constituent quark model which has been applied to a wide range of hadronic observables, being the model parameters, therefore, completely constrained. The Pc(4380)+ and Pc(4450)+ are studied as molecular states composed by charmed baryons and open charm mesons. Several bound states with the proper binding energy are found in the D¯Σc⁎ and D¯⁎Σc channels. We discuss the possible assignments of these states from their decay widths. Moreover, two more states are predicted, associated with the D¯Σc and D¯⁎Σc⁎ thresholds.